Geochronology, geochemistry, and associated tectonics of Permian-Triassic magmas in NW Truong Son Fold Belt - Tran Trong, Hoa; Tadashi, Usuki; Tuan-Anh, Tran; Ching-Ying, Lan; Nguyen, Hoang; Vu Hoang, Ly; Pham Thi, Dung; Pham Ngoc, Can; Tran Thi, Huong; Somsanith, Duangpaseuth; et al. (Vietnam Journal of Earth Sciences, 2026)
The Permian-Triassic igneous rocks of the Truong Son Fold Belt, on the northeastern margin of the Indochina block, formed during Paleotethyan subduction and the subsequent collision with the South China block. Systematic variations in zircon ages, geochemistry, and isotopic compositions are observed from northern Laos toward the Song Ma Suture zone, the collisional boundary with the South China block. In the Xiang Khuang-Muang Khoun (MK) area, 170–200 km from the suture, magmatic rocks (271–253 Ma) include gabbros and I-type granitoids with relatively higher εNd(t) values (-1.5 to -9) and lower 87Sr/86Sri (0.704–0.717). Toward the suture, in the Nam Phao-Kim Cuong area, granitoids dated at 260–251 Ma are predominantly S-type, highly peraluminous granites with intermediate isotopic εNdi values (-7.4 to -9) and 87Sr/86Sri values (0.7115–0.7285). In the Sam Neua (SN) area, closest to the suture, granitoids dated at 251–244 Ma are primarily I-type and minorly S-type, with highly enriched isotopic compositions (εNdi of -8.4 to -14; 87Sr/86Sri between 0.708 and 0.775). The trace-element chemistry of all granitoids indicates volcanic-arc affinities, though signatures also suggest intraplate and post-collisional influences. The association of granitoids with coeval gabbro-diorites in the MK area suggests binary mixing between mantle magmas and Mesoproterozoic crust-derived melts. In contrast, felsic magmas in the SN area likely reflect melting of diverse crustal components, including Paleoproterozoic continental crust of South China affinity. The suture zone-ward younging of magmatism is consistent with slab rollback during the final stages of continental collision.